The evolution of African plant diversity - Linder, H. Peter (Frontiers in Ecology and Evolution, 2014)
Sub-Saharan Africa includes some 45,000 plant species. The spatial patterns of this diversity have been well explored. We can group the species into a set of biogeographical regions (largely co-incident with regions defined for terrestrial vertebrate groups). Furthermore, we know that the diversity is unevenly distributed, with southern Africa (especially the south-western tip) disproportionally species rich, while the West African interior is disproportionally species poor. However, the origins of this diversity have only been explored for two anomalous African Floras (the Tropic-alpine Flora and the Cape Flora), whereas the origins of the diversity of the other floras are still unknown. Here I argue that six floras, with distinct geographical centres, different extra-African affinities, ages of radiation and radiation rates, can be delimited: the Austro-temperate, Tropic-alpine, Lowland forest, Tropic-montane, Savanna and Arid Floras. The oldest flora may be the Lowland forest Flora, and the most recent is the Tropic-alpine, which probably evolved during the Plio-Pleistocene on the summits of the East Africa volcanoes. My results suggest that the most rapidly radiating flora is the Austro-temperate Flora, while the other floras are all diversifying at more or less the same rate, this is also consistent with the current massive species richness in this flora (about half of the African species richness). The Austro-temperate Flora appears to be related to the floras of the other southern continents, the Tropic-alpine Flora to that of the Northern Hemisphere, and the four tropical floras to the tropical regions of the other continents, consistent with the theory of phylogenetic niche conservatism. Current African diversity may be the result of the sequential adding of new floras to the continent. Possibly the species poverty especially of the Lowland forest Flora may be the result of the spread of C4 grasslands and associated regular fires.